Locating Drainage Pattern for Qaraqosh Valley by Merging ETM+ withSPOT Satellite Image. - Aqeel, Ahmed (Iraqi Journal of Science, 2024)
To perform a good interpretation and spatial analysis for remote sensing data likesatellites images, it is better to enhanced these images by using Image Processingtechniques. In the same time to make good interpretation for any study area it isbetter to collect more than one data about this study area. In this research the studyarea located in Qaraqosh District in Southern East of Mosul city north Iraq. Tworemote sensing data are collected about this area; spectral bands of EnhancedThematic Mapper Plus sensor (ETM+) Landsat 7 satellite, and panchromatic band ofSPOT satellite. The spectral bands of Landsat 7 satellite with high spectralresolution (8 bands) with spatial resolution 28.5 meter. While panchromatic bandof SPOT satellite consider as high spatial resolution (10 meter). The mergingtechnique which applied in this search are called Brovey transformation. The sideeffect of this merging caused blurring in merged image. To enhance this blurring,convolution filter has been performed. Finally the enhanced merged image (withhigh spectral and spatial resolution image) is ready to interpretation andclassification.